Toxic metals health risks assessment using the Monte-Carlo approach coupled with modified water quality index evaluation in Maiganga watersheds, Nigeria - Mohammed, Adamu Usman; Aris, Ahmad Zaharin; Ramli, Mohammad Firuz; Mohd Isa, Noorain (Elsevier, 2024)
Geogenic and anthropogenic activities trigger the accumulation of carcinogenic and non-carcinogenic contaminants in the tropical savanna watershed. This study utilized the human health risk assessment model to identify the effects of non-carcinogenic and carcinogenic toxins in the inhabitants of the Maiganga watershed Nigeria through the Monte-Carlo approach. The modified water quality index (MWQI) was employed to assess the health risks linked to drinking water quality. The overall water quality index suggests that the water is safe to drink, Thus, 81 % of the groundwater is suitable for drinking, while 7.1 % is considered poor and unsafe for drinking. NO3, F, Cr, Pb, and Ni are the key carcinogenic and non-carcinogenic contaminants prevalent in Maiganga groundwater. The non-carcinogenic risk derived from open wells ranges from 0.6402 to 23.1994 in children, 0.2673–9.4625 for females, and 0.2101–9.4569 for males. While in boreholes, it varies from 1.2151 to 31.4620 in children, whereas for females and males, it ranges from 0.3279 to 12.4679 and 0.2576–12.4228, respectively. The Monte-Carlo carcinogenic risk of the best-case scenario evaluated for the open well and borehole confirms that water samples sourced from open wells pose a relatively higher risk of cancer inducement. Therefore, the critical non-carcinogenic and carcinogenic contaminants dominating the Maiganga groundwater are NO3, F, Cr, Pb, and Ni. Children are highly susceptible to carcinogenic and non-carcinogenic exposure, followed by females and males. Regulating hazardous pollutants is mandatory for providing clean and safe drinking water to rural communities.